Arts and crafts in the formation of fashion in Ceará and their relationship with the cotton culture (Revista de Ensino em Artes, Moda e Design, 2023)
This article contributes to the investigation of the formative process of the arts and crafts in the establishment of schools for apprentices started in the 19th century. From the vocations oriented to the students, it is associated in the cotton culture of the state, the relationship with the formation of fashion in Ceará in the 20th century. At transformations achieved over time record, among other things, formative proposals, artistic relationships, with emphasis on the connections economics originated from cotton, the driving force behind the textile vocation and consequently, the development and consolidation of fashion education place. The present study is qualitative in nature and adopts  a procedure methodological approach to bibliographic research by selecting and gathering data from monographic studies such as: books, monographs, theses and dissertations related to the topic in question. In addition to documentary research through thecompilation and analysis of documents, archives, newspaper articles, images, imagery and textual records that present relevant data about the teaching processes, configuring the beginning of arts and crafts until the contemporary in fashion education in Ceará – Brazil. The materials were cataloged and analyzed, paying attention to the chronological order of institutionalization of knowledge related to arts and crafts in the state of Ceará, passing through workshops and schools to academic training. The research presents the relationships between arts and crafts and cotton culture in Ceará and its contribution to the development of the textile sector in the state and academic training in fashion today.
Keywords: School of Art and Crafts; Education; Fashion training